Prognostic value of p53 overexpression and c-Ki-ras gene mutations in colorectal cancer - Bell, S M; Scott, N; Cross, D; Sagar, P; Lewis, F A; Blair, G E; Taylor, G R; Dixon, M F; Quirke, P (Gastroenterology (New York, N.Y. 1943), 1993)
Mutations in Ki-ras codon 12 and the p53 gene are common abnormalities in colorectal cancer. The occurrence of p53 overexpression and/or Ki-ras codon 12 mutations were analyzed in 100 colorectal adenomas to determine if they were related to patient survival. p53 overexpression was identified by immunohistochemistry, and Ki-ras codon 12 mutations were detected using the polymerase chain reaction and a restriction enzyme digestion method. p53 overexpression was identified in 45% of tumors, with a higher frequency identified in DNA aneuploid and left-sided tumors than in DNA diploid and right-sided tumors. Mutations in Ki-ras codon 12 were identified in 24% of carcinomas. Individually, mutations in Ki-ras codon 12 or p53 overexpression were not prognostic indicators of survival. However, a statistically significant difference in survival was identified when these two oncogenic abnormalities were analyzed together. The median survival of patients whose tumors contained both oncogenic abnormalities was less than half of that of patients with either alteration alone or without either abnormality. Screening for multiple genetic abnormalities in colorectal cancers excised at surgery may prove to be a useful tool in determining prognosis.